Plan de marketing para la empresa de lácteos “Prodelac” del cantón Alausí, provincia de Chimborazo - Yunga Naula, Segundo Julián (2015)
The developmentof this research, whose main objective isthe development of a"MARKETING PLAN FORDAIRYCOMPANY" PRODELAC"ALAUSI CANTON, Chimborazo", allowing concrete solutionstobusiness problems, especially in areasales.Problems that limitits growth prospectsandmarket positioning. Aware of thestrongcompetition inthe sector, the policies of the companyare willing tolisten to differentproposalsfor improving themarket position. In the research, the methods used: deductive, inductive, analytical and descriptive, techniques such asdirect observation,interviewto Mrcompany manager, surveys ofcustomers and employees,the information came fromprimary and secondary sources. Order to achieve thesestrategic objectives, the administrative toolsobtained duringcollege preparationwere used; whichallowed forthe analysis andpreliminary assessment of thecompany; external analysisthroughPEST analysisandPorter's5Forces, which coulddetermine theEFEmatrix, obtaining an indicatorof 2.73. Formatsurveys and interviewswas designed, the same, we have obtained resultsthe owner,employeesand customers, of which 11 employeesand 397customerswassurveyed, which information was obtainedto create theIFE Matrix, throwing an indicatorof 2.37and then thehigh-impactmatrix, whichled to the discoverythe following strategic objectives: • Study ofnew product introductions. •Establish newDistributionBranches. •Develop anAdvertising. Among the most importantelements of theexternal environment, consider changing theproduction model, thenational governmentis promoting,and are withinthe benefits: reduction of income taxfrom 25% to22%, down 1%eachyear from theyear of theProduction Code; exemptfrom the calculationof theminimum taxincrementalgenerationexpenses fornewjobs orwage increases. In the domesticenvironment,the most importantfactor to considerthe years ofmarket presenceand locationstrategically located inpredominantlylivestock area. TheproposedStrategicMarketingplanrequires an investmentof$ 31.372,18USD, whichallowpositioning in thelocal marketand getwidecompetitive advantage. It is necessarythat the company "PRODELAC" adopted astechnicalbusiness management tooloftenthe marketing plan, which will bringbenefits andbenefits in the shortand medium term